University Assessment of Collaborative Learning in Social Economic - Pérez-Suárez, Macarena; Sánchez-Torné, Isadora (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This educational derivation concurred in testing the impact of a methodological model from the assessment of university students. The study was carried out on 34 young people who were enrolled in a Social Economy (SE) course. The sample was observed during the training and their data were treated in a descriptive analysis. The study found that university students value meaningful learning and active participation in the construction of knowledge about SE. The students value the university education in HE highly, but they demand its improvement. It also identified the need to rework the contents and reformulate the methodological model.